Empirical model of the total transmission of light in turbid media - Ni, Dongqin; Hohmann, Martin (Journal of the Optical Society of America A-Optics Image Science and Vision, 2025)
The objective of this study is to develop an empirical model for the total transmission in turbid media, which will use the optical properties such as the absorption coefficient, scattering coefficient, and anisotropy factor to predict the total transmission. An empirical model based on the relationship between the total transmission and collimated transmission, integrating an error term to account for discrepancies arising from scattering and absorption effects, is introduced. Monte Carlo simulations were employed to generate data across varying optical properties. The model’s parameters were determined through fitting algorithms and further refined using Bayesian inference, ensuring independence among variables. The results demonstrate that while the total transmission can be accurately described across a range of refractive indices, the quality of the model deteriorates with increasing scattering coefficients. This empirical model offers a rapid and reasonably accurate estimation of the total transmission, with potential applications in fields requiring quick assessments of light propagation in turbid media.
CRIS-Team Scopus Importer:2025-02-14